Mediterranean Diet Adherence and Subjective Well-Being in a Sample of Portuguese Adults - Andrade, Vanda (Nutrients, 2020)
The Mediterranean diet (MD) and other lifestyle characteristics have been associated with well-being, a broad multiparameter concept that includes individual’s subjective assessment of their own well-being (SWB). Some studies have suggested that diet influences SWB, thus, this work aimed to add novel information on the association of MD and SWB in a sample of Portuguese adults. Data on sociodemographic, economic, lifestyle, diet, and SWB were collected through a self-filled online questionnaire. MD adherence was assessed by the Mediterranean Diet Adherence Screener (MEDAS) score. Results showed a moderate adherence to the MD in 490 Portuguese adults (mean MEDAS of 7.4 ± 2.1). A higher MD adherence was found to be significantly positively associated with women, employed individuals, a higher number of meals per day, and those with frequent contact with nature (p-value < 0.0025, using Bonferroni adjustment). As a novelty, this study divided the participants into low SWB, medium SWB, and medium to high SWB profiles (3.9 ± 1.0; 6.2 ± 1.0; 8.2 ± 1.3, respectively; p-value < 0.05), which reported significantly increasing MEDAS scores (6.5 ± 2.1; 7.3 ± 2.1; 7.8 ± 1.9; respectively, p-value < 0.05).